Effect of hypocaloric high-protein, low-carbohydrate diet supplemented with fennel on androgenic and anthropometric indices in overweight and obese women with polycystic ovary syndrome: A randomized placebo-controlled trial. (January 2021) - Nadjarzadeh, Azadeh; Ghadiri-Anari, Akram; Ramezani-Jolfaie, Nahid; Mohammadi, Mohammad; Salehi-Abargouei, Amin; Namayande, Seyedeh Mahdieh; Mozaffari-Khosravi, Hassan; Hosseini-Marnani, Elham
Highlights: Polycystic ovary syndrome (PCOS), one of the most common endocrine disorder in women of reproductive age, is associated with insulin resistance and hyperandrogenism. The effect of hypocaloric high-protein, low-carbohydrate weight loss diet supplemented with fennel on anthropometric and androgen indices in overweight and obese women with PCOS were elevated. A randomized trial with factorial design assigned subjects into four groups and followed them for 12 weeks. Adding fennel to the hypocaloric high-protein/standard diets did not result in additional improvements in weight loss (HSDF: -1.78 ± 1.67 kg; HHPF: -3.35 ± 2.47 kg; HSDP: -3.36 ± 2.92 kg; HHPP: -2.28 ± 2.13 kg; P = 0.154). There was no significant difference in changes in anthropometric and androgen indices from baseline to end of study between subjects receiving and not receiving hypocaloric high-protein diet or fennel capsule (P > 0.05). Abstract: Objective: The aim of this study was to evaluate the effect of hypocaloric high-protein, low-carbohydrate weight loss diet supplemented with fennel on anthropometric and androgen indices in overweight and obese women with polycystic ovary syndrome (PCOS). Methods: A randomized controlled trial with a factorial design was performed on sixty-four overweight/obese women with PCOS. Participants were randomly allocated to four groups (n = 16 per group) as follows: 1) hypocaloric standardize diet + fennel (2 capsule/day) (HSDF), 2) hypocaloric high-protein diet + fennel (2 capsule/day) (HHPF), 3) hypocaloric standardize diet + placebo (HSDP), and 4) hypocaloric high-protein diet + placebo (HHPP). Results: The mean (SD) age of the participants was 28.54 (6.80) years and body mass index was 32.24 (4.65) kg/m 2 . At the end of intervention, protein intake was 20.43 % in the groups that received a high-protein diet versus 16.37 % in the standard diet groups (P < 0.001). Combination of hypocaloric high-protein diet and fennel capsule did not significantly affect change in outcomes compared with groups not receiving them. There was a significant interaction between hypocaloric high-protein diet and fennel on weight (P = 0.019). Conclusion: A hypocaloric high-protein diet along with fennel supplementation could not provide additional improvements in anthropometric and androgen indices among PCOS women. Further studies are required to more precisely elucidate these findings.